(untitled) (Journal of Misan Researches, 2021)
The research called " Poetry AL.Hakam bin Qanbar AL.Mazini (Collection, Study and documentation ) " tried to get acquainted with the Scattered Pome of AL.Hakam bin Qanbar in literary and historical books. The research focused on two parts, The first section is to stand on the news and study of his poetry and poetry after Collecting the dispersal in his poetry blog that came within the second section and which was devoted to the rest of the poet’s poetry. Then the research was concluded with the conclusion and last of study and investigation sources.